Formalismo de Hamilton-Jacobi para ações de primeira ordem - Bertin, Mario Cezar Ferreira Gomes [UNESP] (2006)
In this work we develop the general treatment of singular systems via Hamilton-Jacobi formalism, ﬁrst developed b yCaratheódory for regular systems. We will give emphasis on ﬁrst order action systems, whose Lagrangian is a linear function of the velocities. The main objective is, besides presenting the formalism in an appropriate form, to show the existence of a simplectic structure in the phase space of these systems by ﬁnding appropriate generalized brackets, with which the canonic quantization will be given in a natural way